Faktor-faktor Yang Memengaruhi Kualitas Laporan Keuangan Pemerintah: Moderasi Kompetensi Sumber Daya Manusia di BPKAD Kota Surakarta - Anita Nurhidayah; Maya Widyana Dewi; Desy Nur Pratiwi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2026)
This study was conducted with the aim of partially determining the effect of understanding government accounting standards and internal control systems on the quality of financial reports with human resource competency as a moderating variable at the BPKAD of Surakarta City. The population was all 85 employees working at the BPKAD of Surakarta City. The sampling technique used purposive sampling, resulting in a sample of 74 employees. This type of research is quantitative with primary data. Data collection techniques used questionnaires. Data analysis methods used descriptive respondent data, validity tests, reliability tests, and classical assumption tests (normality tests, multicollinearity, heteroscedasticity, and autocorrelation). Hypothesis testing used multiple linear regression tests, F tests, t tests, coefficient of determination tests (adjusted R2) and moderated regression analysis tests. The results of this study are that partially understanding government accounting standards has a positive and significant effect on the quality of financial reports, internal control systems have a positive and significant effect on the quality of financial reports, human resource competency cannot strengthen the effect of understanding government accounting standards on the quality of financial reports, and human resource competency cannot strengthen the effect of internal control systems on the quality of financial reports. Keywords: Financial Report Quality, Human Resource Competence, Internal Control Systems, Understanding of Government Accounting Standards.